The genera Limatula and Limea (Mollusca, Pelecypoda, Limidae) from deep waters off Brazil - de Castro Oliveira, Cléo Dilnei; Absalão, Ricardo Silva (Zootaxa, 2008)
Five species of the genus Limatula and one of Limea were found in a total of 83 samples taken from deep waters (700– 1950 m) off Brazil. Limatula laminifera (Smith, 1885) and Limea lirata Allen, 2004 were not previously reported from Brazil. Limatula confusa (Smith, 1885) and L. louiseae Clarke, 1974, although already reported for Brazilian waters, have their distribution extended southward. Limatula domaneschii n.sp. is described from the Campos Basin (˜22° S). It is diagnosed by concentric lamellae strengthening towards the ventral margin of the shell, and absence of axial ornamentation; an internal median groove is not present. A fifth Limatula species is present, and we strongly suspect that it is also new to science, but a formal description is delayed until additional specimens are collected.